Financial development and central bank bilateral currency swaps: Is there trade effect? - Mohammed, Abdullahi Ahmed (Universitas Islam Indonesia, 2024)
Purpose ― This paper aims to empirically investigate the impact of currency swaps on international trade, given China's differential level of financial development and its currency swap partners. Methods ― The study employes an empirical structural gravity model using datasets encompassing financial development, trade, and intuitive gravity equation variables for 27 countries from 1980 to 2013. The level of financial development and swaps was captured by the interaction term of the disaggregated measure of financial development, such as access, depth, and efficiency, each interacting with currency swaps.Findings ― The findings suggest that currency swaps are essential for trade and exhibit a large trade effect, especially for countries with relatively low levels of financial development. The paper substantiates empirical evidence indicating disparities in financial development across countries, and such differences are important in determining trade patterns. Implication ― Strong financial systems promote trade in advanced economies, whereas the opposite holds true for developing countries. The examination of the influence of financial systems on trade through empirical tests remains important on the research agenda of policymakers and researchers, especially those looking at industry-level import and export data.Originality ― The study delves into the nexus between financial development and trade within the framework of the Central Bank bilateral currency swap network by highlighting the role of financial institutions and market size (depth), activity (access), and efficiency. In addition, it addresses the drawbacks of previous empirical research that largely focuses on the private credit-to-GDP ratio as a key proxy for financial development.